OPTIMASI AMOBILISASI XILANASE DARI Trichoderma viride PADA MATRIKS PASIR LAUT - Laziba, Dihan; Sutrisno, Sutrisno; Suratmo, Suratmo (Jurnal Ilmu Kimia Universitas Brawijaya, 2013)
ABSTRACT Immobilization of xylanase with physical adsorption method on sea sand matrix is carried out to increase stabilization of enzyme and can be reused. Xylanase is isolated from Trichoderma viride, purified by precipitation method by using ammonium sulfate with saturated level of 40-80%. This research is to know the shaking time and optimum concentration of xilanase. Variance of shaking time is (1,2,3,4,5) hour and variance concentrate of xylanase (0.5; 1.5; 2.5; 3.5; 4.5) mg/mL on 0.1 g of sand at room temperature. Content of xylanase enzyme used for immobilization is 4.517 mg/ml with activity was 17.029 units . The results of the research showed that the optimum condition of immobilization xylanase is achieved when shaking time is 2 hours and concentrate of xylanase is 4.5 mg/mL within absorbed xylanase is 205.120 mg/g and activity of immobilizied xylanase is 135.886 units. Keywords: activities, concentration of xylanase, sea sand, shaking time, Trichoderma viride.